Overweight and Obesity among Primary School Going Children in Urban Agra: A Cross-Sectional Study - Iqbal Aqeel Khan; Geetu Singh; Kunver Viresh Singh (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Childhood obesity is global nutritional concern. It is precursor of various non-communicable diseases and metabolic disorders in adulthood. Objective: To determine the prevalence of overweight and obesity among primary school students in urban Agra. Method: This cross-sectional study was done among 200 children studying in grades 1st to 5th in government and private school of Agra. List of all schools in Agra city having 1 to 5 classes was obtained from official website of Agra District Authorities. One government and one private school were selected. 100 students were selected from each selected school. A pre-designed and pre-tested administered questionnaire was used to collect information and anthropometric measurement; height and weight of the student measured to calculate Basal Metabolic Index (BMI). Overweight/obesity was defined using age and sex specific body mass index cut off points. Result: Prevalence of overweight and obesity was 16.5% and 7% respectively. Prevalence of overweight and obesity was more in boys as compared to girls. Obesity is seen only in private school students. Conclusion: In the present study, the magnitude of overweight and obesity is high among boys and children studying in private school. Health education should be given in the schools so as to educate children as well as parents regarding risk factors, preventive measures and the consequences of overweight and obesity.